تأثير عزلة سورية محلية من الفطر Trichoderma harzianum Rifai في تثبيط نمو الفطر المسبب لمرض التبقع الشوكلاتي على الفول (Botrytis fabae Sard) مخبرياً - حسن محمود; الأحمد جمال; تموز منذر (Latakia University Journal -Biological Sciences Series, 2020)
The influence of two isolates of the fungus Trichoderma harzianum (one of them commercial and the other local) were compared in laboratory conditions against Botrytis fabae wich causes Chocolate Spot Disease on faba bean plants (Vicia faba). Results showed that the two isolates have good significant ability to inhibit the studied disease fungus directly or indirectly. The efficacy of the local isolate in the dual culture was significantly better than the commercial one, because it’s inhibiting ability reached 59.5% after 14 days of incubation conditions compared with 47.9% for the commercial one. On other hand, the indirect inhibiting ability, in similar conditions reached 36.8%, 34.8% gradualy due to the influence of volatiles which were producted from each of the two studied isolates, without any significant differences. تمت دراسة كفاءة عزلة محلية من الفطر تريكوديرما Trichoderma harzianum بالمقارنة مع عزلة أخرى تجارية من النوع نفسه في تثبيط نمو عزلة محلية من الفطر Botrytis fabae المسبب لمرض التبقع الشوكلاتي على نبات الفول Vicia faba L. في سوريا ضمن ظروف المختبر في حال التضاد المباشر وفي حال التضاد غير المباشر. أظهرت النتائج مقدرة معنوية لكل من العزلتين المدروستين من الفطر تريكوديرما على تثبيط نمو الفطر الممرض المدروس في حالتي التضاد المباشر أم غير المباشر، وتفوقت العزلة المحلية بشكل معنوي على العزلة التجارية إذ بلغت كفاءتها في تثبيط نمو عزلة الفطر الممرض المدروسة في حال التضاد المباشر بعد 14 يوم من التحضين 59% مقارنة بـ 47.9% على التوالي، في حين بلغت كفاءة التثبيط في حال التضاد غير المباشر والعائد لفعل المنتجات الغازية Volatiles من مستعمرة كل من العزلة المحلية والتجارية 36.8% و34.8% على الترتيب ودون فرق معنوي بينهما.